الإعجاز القرآني في آيات الظل والظلال بين الرؤية العلمية والأسرار البيانية - نصبة فتيحة (University of Eloued جامعة الوادي, 2024)
هذا البحث الموسوم ب:"الإعجاز القرآني في آيات الظل والظلال بين الرؤية العلمية والأسرار البيانية, يهدف إلى الإجابة على إشكالية تتمحور حول: "الكيفية التي توافقت فيها النصوص القرآنية في آيات الظل مع الحقائق العلمية الحديثة", وللإجابة عن هذه الإشكالية يستهل البحث بمفاهيم عامة حول الإعجاز والبيان, ثم يستعرض شرحا لآيات الظل في القرآن الكريم, وفي الجانب التطبيقي يقدم نماذج من آيات الظل يبرز فيها التوافق بين التفسيرات العلمية الحديثة وما ورد من بيان في القرآن الكريم, يخلص البحث من خلالها إلى أن الآيات القرآنية التي تتناول الظل تظهر إعجازا علميا وبيانيا متكاملا. This research, which is tagged with: "Qur'anic miracles in the verses of shadow and shadows between scientific perspective and statement secrets, aims to answer a problem centred on: "How the Qur'anic texts in the verses of the shadow coincided with modern scientific facts," and to answer this problem, the research begins with general concepts about miracles and the statement, then reviews an explanation of the verses of shadow in the Holy Qur'an, and in the applied side, it presents models of shadow verses in which the compatibility between modern scientific interpretations and the statement in the Holy Qur'an is highlighted, through which the research concludes that the Qur'anic verses that deal with shadow show an integrated scientific and bimanical miracle.
ماستر
Keywords: الإعجاز القرآني، الظل وظلال، الرؤية العلمية، البيان; The Miracle of the Qur’an; Shadow and Shadows; Scientific Vision; Statement